Proceedings of the 4th International Conference on Innovation in Education, Science and Culture, ICIESC 2022, 11 October 2022, 2022
DOI: 10.4108/eai.11-10-2022.2325589
|View full text |Cite
|
Sign up to set email alerts
|

Production of Liquid Smoke From the Combination of Coconut Shell and Empty Fruit Bunch through Pyrolysis Process

Abstract: This study aims to produce liquid smoke that will be used as plant pesticide by means of pyrolysis of a mixture of two types of biomass, coconut shells (CS) and empty fruit bunches (EFB). The parameters used are the ratio of the mixture of the two materials and the pyrolyse temperature ranges from 300 to 500 o C. A reactor of 2 kg capacity with indirect heating is used for this study. Heat is obtained from LPG combustion using a burner. Feedstock used in the form of pieces of coconut shells aproximately 5 x 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ratnani stated that liquid smoke produced a percent yield of 23.6% for 360 min with efficiency of 6.5% (Ratnani, Hadiyanto, Widiyanto, & Adhi, 2022). At the same time, Robert Silaban reported that using conventional methods produced a liquid smoke yield of 17.5% for 29 min with efficiency of 60.3% (Silaban, Lubis, Siregar, Sinaga, & N.P, 2022). Baiti Hidayati also explained that liquid smoke produced by conventional means was 23.6% for 165 min with efficiency of 14.3% (Hidayati, Sipahutar, Bizzy, & Faizal, 2022).…”
Section: Comparison Yield Of Conventional and Microwave-assisted Pyro...mentioning
confidence: 98%
“…Ratnani stated that liquid smoke produced a percent yield of 23.6% for 360 min with efficiency of 6.5% (Ratnani, Hadiyanto, Widiyanto, & Adhi, 2022). At the same time, Robert Silaban reported that using conventional methods produced a liquid smoke yield of 17.5% for 29 min with efficiency of 60.3% (Silaban, Lubis, Siregar, Sinaga, & N.P, 2022). Baiti Hidayati also explained that liquid smoke produced by conventional means was 23.6% for 165 min with efficiency of 14.3% (Hidayati, Sipahutar, Bizzy, & Faizal, 2022).…”
Section: Comparison Yield Of Conventional and Microwave-assisted Pyro...mentioning
confidence: 98%